2022
DOI: 10.3390/antibiotics11050668
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Silver and Gold Nanoparticle Formation Using Endophytic Fungi as Powerful Antimicrobial and Anti-Biofilm Potentialities

Abstract: Nanotechnology is emerging as a new technology with encouraging innovations. Global antibiotic use has grown enormously, with antibiotic resistance increasing by about 80 percent. In view of this alarming situation, intensive research has been carried out into biogenic nanoparticles and their antibacterial, antifungal, and antitumor activities. Many methods are available to enhance stability and dispersion via peroration of conjugate with a polymer, such as chitosan, and other bioactive natural products. Two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Silv2 and Alternaria sp. Gol2 were used for the biological synthesis of Ch-silver and Ch-gold nanocomposites [ 72 ].…”
Section: Biosynthesis Of Ch-coated Polymeric Silver and Gold Nanopart...mentioning
confidence: 99%
“…Silv2 and Alternaria sp. Gol2 were used for the biological synthesis of Ch-silver and Ch-gold nanocomposites [ 72 ].…”
Section: Biosynthesis Of Ch-coated Polymeric Silver and Gold Nanopart...mentioning
confidence: 99%
“…Further, research by Mostafa et al (2022) also showed that chitosan-silver NPs and chitosan-gold NPs conjugates have promising broad-spectrum anti-biofilm activity against Bacillus subtilis , P. aeruginosa , S. aureus , and E. coli. Silver NPs combined with a dopamine and an α-amylase coating showed the reduction of S. aureus biofilms on titanium surfaces . AgNPs showed higher activity as compared to AuNPs.…”
Section: Nanotechnological Approaches For Biofilm Controlmentioning
confidence: 99%
“…The antibiofilm potential of these conjugates was checked against four biofilm-forming bacteria such as P. aeruginosa , E. coli , B. subtilis , and S. aureus . The results displayed a significant antibiofilm potential of chitosan–AgNPs conjugate when compared with chitosan–AuNP conjugates [ 144 ].…”
Section: Antibiofilm and Anti Quorum Sensing Activities Of Mycogenic ...mentioning
confidence: 99%